Performance Evaluation of Cooperative Spectrum Sensing Algorithm Based on Quantum Manta Ray Algorithm - Chen, Jun; Huang, Yiping; Wang, Tianyi; Zhang, Ling; Li, Yuqian (IEEE access, 2024)
In order to address the issue of limited sensing accuracy in traditional spectrum sensing algorithms within low SNR communication environments, a novel multi-node cooperative sensing method is proposed in this work. In this approach, each node utilizes a stochastic resonance sensing model for information detection, while the OR criterion is employed to fuse information from multiple nodes. In situations where user presence cannot be reliably determined, each node simultaneously transmits signal energy values and SNR for weighted fusion. Morevover, the weighted fusion stage focuses primarily on determining the weight coefficients of each node. To achieve this efficiently, a Quantum Manta-Ray Optimization Algorithm capable of selecting these weights effectively, is proposed. While comparing with the other existed methods, this method can exhibits superior sensing efficiency and get the excellent sensing performance.The algorithm's perceptual accuracy is enhanced by over 5%.